Polylactic acid-based high-performance implantable biomedical product and preparation method thereof

By using a micro injection molding process in situ fiber-forming PBSA dispersed phase in polylactic acid matrix and adding a specific content of hydroxyapatite, the non-degradability and bioincompatibility of existing bone nail materials are solved, and high performance is achieved , the preparation of bioresorbable bone nails reduces production costs and improves therapeutic effects.

CN119455132AActive Publication Date: 2025-02-18SICHUAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411485368.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-18
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing bone nail materials have problems such as non-degradability, bioincompatibility and the need for secondary surgical removal, which is difficult to meet the demand for high-performance and bioresorbable materials during fracture healing.

Method used

In situ fibrillated PBSA dispersed phases in polylactic acid (PLA) matrix are combined with specific contents of hydroxyapatite (HA) to improve the toughness and osteoinductive activity of the material.

Benefits of technology

The high toughness and osteoinductive activity of polylactic acid-based bone nails are achieved, which reduces production costs, avoids the need for secondary surgery, and improves the treatment effect and safety of patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455132A_ABST
    Figure CN119455132A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance implantable biomedical product based on polylactic acid and a preparation method thereof.The preparation method comprises the steps that by weight, 10-20 parts of poly (butylene succinate-adipate) and 1-2 parts of hydroxyapatite are subjected to melt blending to prepare a PBSA / HA mixture; mixing 78-89 parts of polylactic acid with PBSA / HA, carrying out melt blending extrusion through a twin-screw extruder, and granulating to obtain PLA / PBSA / HA granules; finally, the PLA / PBSA / HA granules are prepared into the high-performance implantable biomedical product through a micro injection molding process. According to the method, in-situ fiber forming of a PBSA dispersed phase in a PLA matrix is achieved through induction of a micro injection molding process under the condition of a strong shear force field, meanwhile, the toughness of the product is unexpectedly and remarkably improved by adding a specific content of hydroxyapatite, and the prepared product has excellent biocompatibility and bone induction activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of injection molding of implantable medical products, and relates to a high-performance implantable biomedical product based on polylactic acid and a preparation method thereof, and in particular to the preparation of a high-performance polylactic acid-based bone nail that can be implanted in the human body. Background Art

[0002] With the acceleration of global population aging, the incidence of fractures is increasing every year. Therefore, bone damage caused by fractures has become a major health problem, especially affecting the elderly. Although bone tissue has the ability to self-repair, this intrinsic ability is mainly effective in cases of mild bone damage. For larger bone defects, fracture internal fixation is required to promote complete healing of the damaged area. The coordinated fixation of steel plates and bone screws is a common method for treating fractures, among which the use of bone screws to fix fracture fragments is a key step in orthopedic surgery. Therefore, the quality of bone screws has become an important factor affecting the patient's postoperative recovery. Metal alloys have obvious advantages, including extremely high mechanical properties, high reliability and easy processing, making them the earliest bone repair materials used in clinical practice. However, metal materials also have obvious disadvantages, such as non-degradability, biological inertness, shielding effect, rejection reaction, metal ion leaching and other problems. It is particularly inconvenient that a secondary operation is required to remove the metal implant after bone healing. This not only causes pain to the patient, but also increases the risk of re-fracture. Therefore, the development of a new generation of fracture internal fixation devices with bioresorbable properties has become an important demand in the field of orthopedic medicine.

[0003] Bioresorbable polymers have significant advantages over metal alloys in bone repair, especially their excellent biocompatibility and bioresorbability. Therefore, bioresorbable polymers can promote a more effective healing process and avoid the need for secondary surgery. To date, there are limited reports in the literature on polymer-based bioresorbable bone nails. For example, Liu et al. documented a bone fixation material made of silk protein, which was designed for cranial fixation in neurosurgery. Their study demonstrated the feasibility of this material through a one-year animal model experiment. The results showed that this cranial fixation system has excellent biocompatibility, so it does not cause foreign body reactions, does not produce harmful substances after degradation, and does not hinder X-ray imaging (K. Liu, Z. Shi, S. Zhang, Z. Zhou, L. Sun, T. Xu, Y. Zhang, G. Zhang, X. Li, L. Chen, Y. Mao, TH Tao, A Silk Cranial Fixation System for Neurosurgery, Advanced Healthcare Materials 7 (6) (2018) e1701359-1701372.). Zhang et al. developed a shape memory bone screw composed of polyurethane, hydroxyapatite and arginylglycyl aspartic acid. This bone screw exhibits significantly enhanced mechanical properties, with a modulus of 250MPa, and has significant shape memory ability, which can quickly recover its original shape within 20 seconds. In vitro evaluation showed that this bone screw not only promoted cell adhesion, but also stimulated the proliferation and differentiation of bone marrow mesenchymal stem cells into osteoblasts (Y. Zhang, J. Hu, R. Xie, Y. Yang, J. Cao, Y. Tu, Y. Zhang, T. Qin, X. Zhao, A programmable, fast-fixing, osteo-regenerative, biomechanically robust bonescrew, Acta Biomaterialia 103 (2020) 293-305.). Cai et al. synthesized a resorbable high-strength thermosetting polymer, poly (glycerol succinate) (PGS). This material has a flexural strength of 122MPa and shows great potential in bone fixation applications. In vitro evaluation showed that PGS promoted cell adhesion and proliferation.In addition, after implanting PGS bone screws into rabbit bones and subsequently evaluating them for 12 weeks, tomography and histological analysis showed that PGS screws were successfully integrated with bone tissue (M. Cai, H. Liu, Y. Jiang, J. Wang, S. Zhang, A high-strength biodegradable thermoset polymer for internal fixation bone screws: Preparation, in vitro and in vivo evaluation, Colloids Surf B Biointerfaces 183 (2019) 110445-110455.). However, we note that although the above methods can all prepare bone screws (bone screws), they all use relatively complex processes to achieve better technical effects. They are typical laboratory technologies with disadvantages such as low production efficiency, high cost, and low product qualification rate. Therefore, it is necessary to develop advanced processing technologies for large-scale mass production of bone screws to reduce the production cost of bone screws, which is undoubtedly of great significance to reducing the cost of patient treatment.

[0004] Among bioresorbable polymers, synthetic polymers are preferred over natural polymers due to their controllable degradation rate and excellent mechanical properties. Polylactic acid (PLA) is a bioresorbable synthetic polyester that has been approved by the US FDA for use as a fracture fixation material in clinical treatment. Although PLA has high mechanical strength, its low toughness, poor osteoinductive activity, and acidic degradation products hinder its widespread application in bone repair.

[0005] To solve the above problems of PLA, especially to improve its toughness and osteoinductive activity, has become a key issue in the development of biodegradable bone fixation devices. However, due to the lack of osteoconductivity of PLA, enhancing its mechanical properties alone may not be sufficient to achieve effective bone fixation.

[0006] Hydroxyapatite (HA) is the main inorganic mineral component of human bones. Due to its excellent osteoconductivity and biocompatibility, it is often used as a raw material for bone repair tissue. Therefore, introducing HA into the material system is a promising method to improve the osteoinductive activity of PLA. However, as an inorganic filler, hydroxyapatite itself has poor toughness and needs to be compounded with biodegradable and biocompatible polymers to improve its toughness.

[0007] In the currently published technical literature, the introduction of HA has been widely involved in related research. However, relevant researchers have found that adding excessive HA fillers (such as 8-10wt%) will increase the brittleness of the corresponding composite materials, seriously deteriorate the toughness of the products and affect their formability. In other reports, some researchers have tried to reduce the degree of deterioration of the toughness of the products by adding a small amount of HA (4wt%), but the effect is not ideal. Summary of the invention

[0008] In order to solve the problems in the background technology, the present invention provides a high-performance implantable biomedical product based on polylactic acid and a preparation method thereof. The method is to induce a strong shear force field condition through a micro-injection molding process to achieve in-situ fiberization of a PBSA dispersed phase in a PLA matrix, and at the same time combine the addition of a specific content of hydroxyapatite to achieve an unexpected and significant improvement in the toughness of the product. The prepared product has excellent biocompatibility and bone induction activity.

[0009] To achieve the above-mentioned purpose, the present invention is implemented by adopting a technical solution consisting of the following technical measures.

[0010] A method for preparing a high-performance implantable biomedical product based on polylactic acid, which mainly comprises the following steps:

[0011] (1) Prepare the following raw materials by weight:

[0012] Polylactic acid (PLA) 78-89 parts,

[0013] Polybutylene succinate adipate (PBSA) 10-20 parts,

[0014] Hydroxyapatite (HA) 1-2 parts,

[0015] Wherein, the polylactic acid, polybutylene succinate adipate and hydroxyapatite are 100 parts in total;

[0016] (2) preparing a PBSA / HA mixture by melt blending the polybutylene succinate adipate prepared in step (1) and hydroxyapatite;

[0017] (3) mixing the polylactic acid prepared in step (1) with the PBSA / HA mixture obtained in step (2), adding the mixture to a twin-screw extruder and extruding the mixture at 180-200° C. and 100-200 rpm, and using a traction machine to stably traction the extruded filaments, cooling and pelletizing the mixture to obtain PLA / PBSA / HA pellets;

[0018] (4) injecting the PLA / PBSA / HA pellets obtained in step (3) into a desired product mold cavity in a micro injection molding machine, and preparing a high-performance implantable biomedical product through a micro injection molding process;

[0019] The process conditions of micro injection molding are as follows: injection speed 50-600 mm / s, mold temperature 20-60°C, melt temperature 180-200°C, holding pressure and cooling time 5-15s, and the shear rate of the blend at the gate in the micro injection molding machine is controlled to be 50,000-70,000s. -1 .

[0020] It should be noted that the preparation method of the present invention is based on a micro-injection molding process, and in particular, adopts the principle of in-situ fiberization. The strong shear force field conditions induced by the micro-injection molding process promote the in-situ fiberization of PBSA in the PLA matrix, thereby improving the mechanical properties of the composite material. The process conditions of the micro-injection molding process described in step (4) are all necessary conditions to meet the in-situ fiberization.

[0021] For a detailed explanation of the in-situ fiber-forming principle and the necessity of the process conditions of the micro-injection molding process described in step (4), please refer to the applicant's previously authorized invention patents "Method for preparing PLA biomedical micro-devices by micro-injection molding process" (CN110815700B) and "Method for preparing high-performance PLA / PBSA micro-products based on micro-injection molding process" (CN114228086B).

[0022] The invention of the present invention is that, based on the applicant's previously authorized invention patent "Method for preparing high-performance PLA / PBSA micro-products based on micro-injection molding process" (CN114228086B), in order to improve the biocompatibility and osteoinductive activity of the product, when trying to add hydroxyapatite (HA) into the system, it was accidentally discovered that under certain conditions, the addition of HA will significantly promote the toughness of the PLA / PBSA system micro-injection molded samples, and the elongation at break of the samples will increase by more than 10%, which is obviously contrary to the common sense that adding HA will deteriorate the toughness of the material system in traditional cognition. However, when the addition amount of HA is above 4wt%, the sample shows obvious deterioration in toughness.

[0023] Generally, the polylactic acid in step (1) can be selected as left-handed or right-handed polylactic acid according to the actual product use and functionality, and those skilled in the art can select polylactic acid of appropriate molecular weight according to specific needs, preferably polylactic acid currently used in implantable medical products / devices, for example, any one of polylactic acid types 4032D, 6201D, 3251D, and 7000D.

[0024] Generally, the polybutylene succinate adipate in step (1) can be selected according to actual needs to have different molecular weights, such as injection molding grade, blow molding grade, etc. to achieve different viscosity ratios between PLA and PBSA to meet actual processing needs.

[0025] It is worth noting that the melt blending in step (1) is usually carried out because PBSA and HA are hygroscopic and moisture easily causes polymer depolymerization during the melt blending process. Therefore, PBSA and HA need to be dried at 50° C. and 80° C. for at least 8 hours, respectively. Those skilled in the art can select an appropriate drying time according to the actual processing volume.

[0026] Herein, the PBSA / HA mixture is prepared by melt blending in step (2). A conventional melt blending process technology known in the art can be selected, which is intended to make PBSA and HA form a mixture in which HA is evenly dispersed, such as using an internal mixer for melt blending.

[0027] In one technical solution, the step (2) comprises melt blending the polybutylene succinate adipate prepared in the step (1) with hydroxyapatite to prepare a PBSA / HA mixture, specifically melt blending the prepared polybutylene succinate adipate with hydroxyapatite in an internal mixer to prepare a PBSA / HA mixture;

[0028] The process parameters for melt blending in the internal mixer are as follows: rotor speed is 30-80 rpm, blending time is 5-7 minutes, and temperature is 110-130°C.

[0029] In this article, the PLA / PBSA / HA pellets are obtained by cooling and pelletizing in step (3), and the pellet size and shape should be suitable for subsequent micro injection molding. Generally speaking, those skilled in the art can select suitable pellet size and shape according to the micro injection molding equipment used. In one technical solution, the particle size of the PLA / PBSA / HA pellets is preferably 0.5 to 2 mm.

[0030] It should be noted that the PLA added in step (3) is usually hygroscopic, and moisture can easily lead to polymer depolymerization during the extrusion process. Therefore, the PLA needs to be dried at 80° C. for at least 8 hours. Those skilled in the art can select an appropriate drying time based on the actual processing volume.

[0031] It is worth noting that the present invention limits the extrusion of step (2) through a twin-screw extruder at a limited condition of 100 to 200 rpm because the dispersed phase will form nano-scale spherical particles dispersed in the PLA matrix under the action of a strong shear force field, and more nanofiber bundles can be formed in the later micro-injection molding process, so the use of a twin-screw extruder is limited. If the extrusion speed is too low, it is not easy to form a sea-island structure blend with a nano-scale dispersed phase; if the extrusion speed is too high, although a nano-scale dispersed phase can be obtained, the PLA molecular chain breaks, and severe degradation occurs, resulting in reduced mechanical properties.

[0032] In this article, the high-performance implantable biomedical product is prepared by the microinjection molding process described in step (4), and different implantable medical products, such as bone nails, can be prepared by different microinjection molds.

[0033] In this article, the addition amount of polybutylene succinate adipate (PBSA) is limited to 10-20 parts because the inventors of the present invention have found in the actual production process that the addition of PBSA in the micro injection molding process can obviously improve the elongation at break of PLA, but its essence is to form a fibrous structure under certain process conditions. However, when the PBSA content increases, the strength and modulus of the product decrease significantly. In order to improve the elongation at break while maintaining high strength and modulus, the addition amount of PBSA is limited to 10-20 parts, and more preferably 10-15 parts. With reference to the technical solution of the present invention, the material obtained by preparing the obtained material at a PBSA addition amount of 10% shows a material mechanical property significantly higher than the material mechanical property of the same proportion PBSA addition amount prepared by traditional injection molding, and even much higher than the material mechanical property of the material mechanical property of the preferred proportion PBSA addition amount in the traditional injection molding preparation technology. According to the inventors of the present invention, micro injection molding can produce a certain temperature and shear stress gradient in the thickness direction of the mold cavity, thereby forming a "skin layer-core layer" structure in the micro injection molding sample. The morphology images at different positions along the thickness direction show that the PBSA dispersed phase basically exists in the skin layer in the form of spherulites or ellipsoids, while in the shear layer and core layer, the PBSA dispersed phase can form long and interlocking fibrous structures.

[0034] Further, the process conditions of the micro injection molding process described in step (4) include an injection speed of 50 to 600 mm / s. The inventors of the present invention found during the experiment that different injection speeds include 0 mm / s (replaced by hot pressing), 20 mm / s, 50 mm / s and 100 mm / s. In the morphology comparison results, it can be seen that the injection speed has a great influence on the morphology formation. For the hot pressing molded sample (here refers to the injection speed = 0 mm / s), an island structure is formed, and the PBSA dispersed phase does not undergo fiberization. In contrast, under micro injection molding conditions, when the injection speed is in the range of 20 to 100 mm / s, the PBSA dispersed phase structure formed is completely different. In the PLA continuous phase matrix, HA filler particles are contained, forming a large number of fibrous structures of the PBSA dispersed phase. With the increase of the injection speed (20→100 mm / s), the aspect ratio, orientation degree and number of the fibrous structure of the PBSA dispersed phase also show a significant increasing trend. The formation mechanism involved is attributed to the presence of an extremely strong shear stress field under microinjection molding conditions, which induces the PBSA dispersed phase to form a clear fibrous structure. During the microinjection molding process, the deformation, stretching and orientation of the PBSA dispersed phase droplets along the melt flow direction lead to the formation of fibrous structures. Higher injection speeds lead to the generation of a stronger shear stress field, which in turn leads to the formation of a larger number of fibrous structures of the PBSA dispersed phase with a higher aspect ratio.

[0035] However, due to the differences in micro-injection molded products, and considering that the polymer fluid velocity field distribution depends on the mold structure size, the rheology of the polymer material, the thermal conductivity, the specific processing technology, and the melt flow rate that the injection molding machine can provide, not all micro-injection molding process conditions can make the shear rate equivalent to the range corresponding to the 50-600 mm / s injection speed of the injection molding machine used by the inventor. Therefore, it is particularly important to study at what shear rate a microfibrillated structure can be formed, so as to provide theoretical guidance for product design and process optimization. In view of this, the present invention performs a computer simulation of the injection molding process of PLA / PBSA, calculates the shear rate generated when the melt flows through the gate, and finds that the melt shear rate exceeds 150,000s -1 When the shear rate is 60000s -1 When the shear rate at the gate is 50000~70000s -1 When the fiber morphology of the prepared product is good, the mechanical properties are significantly improved; in this way, those skilled in the art can use fluid finite element simulation software Polyflow to design the gate and runner in advance when designing the product according to the above data, or optimize the processing technology during the actual production process, so that the shear rate at the flow field is at or near the optimal level, thereby reducing the workload of process control.

[0036] In one of the technical solutions, the mold temperature in step (4) is preferably 25-35°C. PBSA, as a dispersed phase, is stretched by the shear flow field to become a fiber, and its specific surface area increases significantly, which is an entropy reduction process. The effect of surface tension causes it to undergo sinusoidal disturbances, which in turn leads to fiber breakage, so a fast cooling rate is required to fix its morphology. According to traditional mold heat transfer theory, the cooling rate of injection molded products during the cooling process is mainly determined by the melt temperature, mold temperature and thermal conductivity of the material. The inventors of the present invention have found in their research that mold temperature has a very large influence on the fibrosis of PBSA, especially for the preparation of micro medical devices with a local thickness of about 0.33 mm and a relatively large area in the perpendicular thickness direction, such as vascular clamps. When the mold temperature is 50°C, the formed fibrous structure is easily broken into small droplets, but when the mold temperature drops to 40°C, it is more fibrous with a few droplets. When the mold temperature drops to 30°C, the droplets almost disappear, and string crystals are attached to the fiber surface. This is mainly because the overall cooling rate inside the product is extremely fast due to the lower mold temperature, and the fibers are cooled and fixed before they can deform or break. When the mold temperature is 25-35°C, the microfiber structure of the product is easier to preserve. The optimization of this technical content has guiding significance for actual production and processing. In some medical products such as micro vascular clips, the curved part is thinner and cools faster, and it is the key part. Whether the internal morphology of this part, that is, the fibrotic structure, can be cooled and fixed in time often determines whether the product is usable.

[0037] In addition, it is well known in the art that in traditional polymer injection molding, the thickness of the injection molded product is relatively uniform, the shear rate is low, and it is difficult to use its own structure to produce in-situ fiberization. Therefore, if it is necessary to improve the mechanical properties of such products through fibrotic structures, the shear rate at the runner and gate during the micro injection molding process will be crucial for the formation of fibrotic structures. For example, for medical devices such as vascular clips and bone nails, those skilled in the art can design the dimensions of the runner or gate based on the technical content of the present invention to construct a shear-stretching flow field to guide actual production and processing.

[0038] It is worth noting that the micro-injection molding machines used in the micro-injection molding process often have large differences in injection pressure and injection speed in their processing conditions due to different models, product requirements and actual conditions. The present invention eliminates the differences caused by different processing environments by providing the shear rate at the runner and the gate during the injection molding process. This enables technical personnel in this field to determine the specific processing conditions suitable for the current processing environment by simulating and calculating the shear rate, and stably obtain high-performance implantable biomedical products with a fibrotic structure without having to perform pre-production operations such as trial molds, thereby greatly reducing production costs.

[0039] The present invention has the following beneficial effects:

[0040] 1. The present invention provides a high-performance implantable biomedical product based on polylactic acid and a preparation method thereof. The method is to induce a strong shear force field condition through a micro-injection molding process to achieve in-situ fiberization of the PBSA dispersed phase in a PLA matrix, and at the same time combine the addition of a specific content of hydroxyapatite to achieve an unexpected and significant improvement in the toughness of the product. The prepared product has excellent biocompatibility and bone induction activity.

[0041] 2. The present invention provides a high-performance implantable biomedical product based on polylactic acid and a preparation method thereof, which is a further extended research and development result based on the applicant's prior authorized invention patent "Method for preparing high-performance PLA / PBSA micro-products based on micro-injection molding process" (CN114228086B). On the basis of inheriting the excellent technical effects of the prior patent technology, the toughness of the prepared product is further improved, and it is endowed with relatively excellent biocompatibility and bone induction activity.

[0042] 3. The present invention provides a high-performance implantable biomedical product based on polylactic acid and a preparation method thereof. By selecting a specific amount of hydroxyapatite added, the elongation at break of the product is ten times or more higher than that of pure PLA products. At the same time, by optimizing the raw material formula, the product also exhibits excellent bending resistance and stiffness. In addition, the results of in vitro biological experiments have confirmed that the prepared micro-bone nail product has the ability to promote cell adhesion, proliferation and differentiation, and the results of animal model experiments have proved its ability to enhance osteoblast proliferation and bone growth, thus making the technical solution of the present invention a promising candidate for orthopedic implantable medical products. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The SEM images of the freeze-quenched cross-section of the intermediate products of Examples 1 to 2 and Comparative Examples 1 to 2 of the present invention and the final prepared samples. Among them, Figures (a) to (d) correspond to the intermediate products obtained in step (3); (a-1) to (d-1) correspond to the cross-section of the final prepared sample parallel to the melt flow direction; (a-2) to (d-2) correspond to the cross-section of the final prepared sample after etching to remove the amorphous phase; (a), (a-1) (a-2) correspond to PPH0; (b), (b-1) (b-2) correspond to PPH1; (c), (c-1) (c-2) correspond to PPH2; (d), (d-1) (d-2) correspond to PPH4.

[0044] Figure 2 This is a TEM image of the intermediate product PLA / PBSA / HA pellets of Example 2 of the present invention, wherein the PBSA phase is located in the dark area in the center, the PLA phase is located in the bright area around, and HA is distributed in the small dark area in the matrix.

[0045] Figure 3 The particle size statistics and comparison bar graph of the PBSA phase in the intermediate products of Examples 1 to 2 and Comparative Examples 1 to 2 of the present invention are shown in FIG. 1. (a) corresponds to the intermediate product obtained in step (3) of Comparative Example 1; (b) corresponds to the intermediate product obtained in step (3) of Example 1; (c) corresponds to the intermediate product obtained in step (3) of Example 2; (d) corresponds to the intermediate product obtained in step (3) of Comparative Example 2.

[0046] Figure 4 The SEM images of the samples finally prepared in Examples 2-3 and Comparative Examples 3-4 of the present invention are shown in Figure 1. (a) corresponds to the sample prepared in Comparative Example 3; (b) corresponds to the sample prepared in Comparative Example 4; (c) corresponds to the sample prepared in Example 3; (d) corresponds to the sample prepared in Example 2.

[0047] Figure 5 The mechanical properties characterization results of the samples finally prepared in Examples 1 to 2 of the present invention and Comparative Examples 1, 2, and 5 are shown in Figure 1. (a) is a typical stress-strain curve; (b) is a comparison of the results of tensile strength, elongation at break, and Young's modulus; (c) and (d) are SEM images of the PPH2 sample after tensile testing (parallel to the melt flow direction and perpendicular to the melt flow direction, respectively); (e) and (f) are 2D-SAXS images of the PPH0 and PPH2 samples after tensile testing.

[0048] Figure 6 The morphology observation and characterization diagram of the samples finally prepared in Examples 1 to 2 and Comparative Examples 1 to 2 of the present invention. Among them, (a) is a digital photo of the PPH2 sample including the flow channel; (b) is a photo of the samples of Examples 1 to 2 and Comparative Examples 1 to 2 before and after the bending test; (c) is a photo of the three-point bending test experiment; (d) is a SEM image of the PPH2 sample; (e) is a local enlarged view of the thread of the PPH2 sample; (f) is a cross-sectional SEM image of the PPH2 sample after etching along the melt flow direction; (g) and (h) are SEM images of the PPH2 sample at different magnifications after the three-point bending test; (i) is the load-displacement curve of the samples of Examples 1 to 2 and Comparative Examples 1 to 2 during the three-point bending test.

[0049] Figure 7 The cytotoxicity results of different samples finally prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 2 are shown in Figure 1. The calcein-AM / PI staining results of the samples of Examples 1 to 2 and Comparative Examples 1 to 2 after co-culturing with cells for 1 day, 4 days and 7 days are shown in Figure 1. DETAILED DESCRIPTION

[0050] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.

[0051] A method for preparing a high-performance implantable biomedical product based on polylactic acid, which mainly comprises the following steps:

[0052] (1) Prepare the following raw materials by weight:

[0053] Polylactic acid (PLA) 78-89 parts,

[0054] Polybutylene succinate adipate (PBSA) 10-20 parts,

[0055] Hydroxyapatite (HA) 1-2 parts,

[0056] Wherein, the polylactic acid, polybutylene succinate adipate and hydroxyapatite are 100 parts in total;

[0057] (2) preparing a PBSA / HA mixture by melt blending the polybutylene succinate adipate prepared in step (1) and hydroxyapatite;

[0058] (3) mixing the polylactic acid prepared in step (1) with the PBSA / HA mixture obtained in step (2), adding the mixture to a twin-screw extruder and extruding the mixture at 180-200° C. and 100-200 rpm, and using a traction machine to stably traction the extruded filaments, cooling and pelletizing the mixture to obtain PLA / PBSA / HA pellets;

[0059] (4) injecting the PLA / PBSA / HA pellets obtained in step (3) into a desired product mold cavity in a micro injection molding machine, and preparing a high-performance implantable biomedical product through a micro injection molding process;

[0060] The process conditions of micro injection molding are as follows: injection speed 50-600 mm / s, mold temperature 20-60°C, melt temperature 180-200°C, holding pressure and cooling time 5-15s, and the shear rate of the blend at the gate in the micro injection molding machine is controlled to be 50,000-70,000s. -1 .

[0061] It should be noted that the preparation method of the present invention is based on a micro-injection molding process, and in particular, adopts the principle of in-situ fiberization. The strong shear force field conditions induced by the micro-injection molding process promote the in-situ fiberization of PBSA in the PLA matrix, thereby improving the mechanical properties of the composite material. The process conditions of the micro-injection molding process described in step (4) are all necessary conditions to meet the in-situ fiberization.

[0062] For a detailed explanation of the in-situ fiber-forming principle and the necessity of the process conditions of the micro-injection molding process described in step (4), please refer to the applicant's previously authorized invention patents "Method for preparing PLA biomedical micro-devices by micro-injection molding process" (CN110815700B) and "Method for preparing high-performance PLA / PBSA micro-products based on micro-injection molding process" (CN114228086B).

[0063] The invention of the present invention is that, based on the applicant's previously authorized invention patent "Method for preparing high-performance PLA / PBSA micro-products based on micro-injection molding process" (CN114228086B), in order to improve the biocompatibility and osteoinductive activity of the product, when trying to add hydroxyapatite (HA) into the system, it was accidentally discovered that under certain conditions, the addition of HA will significantly promote the toughness of the PLA / PBSA system micro-injection molded samples, and the elongation at break of the samples will increase by more than 10%, which is obviously contrary to the common sense that adding HA will deteriorate the toughness of the material system in traditional cognition. However, when the addition amount of HA is above 4wt%, the sample shows obvious deterioration in toughness.

[0064] Generally, the polylactic acid in step (1) can be selected as left-handed or right-handed polylactic acid according to the actual product use and functionality, and those skilled in the art can select polylactic acid of appropriate molecular weight according to specific needs, preferably polylactic acid currently used in implantable medical products / devices. In one embodiment, for example, any one of polylactic acid types 4032D, 6201D, 3251D, and 7000D is selected.

[0065] Generally, the polybutylene succinate adipate in step (1) can be selected according to actual needs to have different molecular weights, such as injection molding grade, blow molding grade, etc. to achieve different viscosity ratios between PLA and PBSA to meet actual processing needs.

[0066] It is worth noting that the melt blending in step (1) is usually due to the fact that PBSA and HA are hygroscopic. During the melt blending process, moisture easily causes polymer depolymerization. In one embodiment, PBSA and HA are dried at 50° C. and 80° C., respectively, for at least 8 hours. Those skilled in the art can select an appropriate drying time according to the actual processing volume.

[0067] In one embodiment, the polylactic acid in step (1) is 78 to 89 parts, for example, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts or any range or point value therebetween; the polybutylene succinate adipate is 10 to 20 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts or any range or point value therebetween.

[0068] Herein, the PBSA / HA mixture is prepared by melt blending in step (2). A conventional melt blending process technology known in the art can be selected, which is intended to make PBSA and HA form a mixture in which HA is evenly dispersed. In one embodiment, for example, an internal mixer is used for melt blending.

[0069] In one embodiment, the step (2) comprises melt blending the polybutylene succinate adipate prepared in step (1) with hydroxyapatite to prepare a PBSA / HA mixture, specifically melt blending the prepared polybutylene succinate adipate with hydroxyapatite in an internal mixer to prepare a PBSA / HA mixture;

[0070] The process parameters for melt blending in the internal mixer are as follows: rotor speed is 30-80 rpm, blending time is 5-7 minutes, and temperature is 110-130°C.

[0071] In this article, the PLA / PBSA / HA pellets are obtained by cooling and pelletizing in step (3), and the pellet size and shape should be suitable for subsequent micro injection molding. Generally speaking, those skilled in the art can select suitable pellet size and shape according to the micro injection molding equipment used. In one embodiment, the particle size of the PLA / PBSA / HA pellets is preferably 0.5 to 2 mm.

[0072] It should be noted that the PLA added in step (3) is generally hygroscopic, and moisture can easily lead to polymer depolymerization during the extrusion process. In one embodiment, the PLA is dried at 80° C. for at least 8 hours. Those skilled in the art can select an appropriate drying time based on the actual processing volume.

[0073] It is worth noting that the present invention limits the extrusion of step (2) through a twin-screw extruder at a limited condition of 100 to 200 rpm because the dispersed phase will form nano-scale spherical particles dispersed in the PLA matrix under the action of a strong shear force field, and more nanofiber bundles can be formed in the later micro-injection molding process, so the use of a twin-screw extruder is limited. If the extrusion speed is too low, it is not easy to form a sea-island structure blend with a nano-scale dispersed phase; if the extrusion speed is too high, although a nano-scale dispersed phase can be obtained, the PLA molecular chain breaks, and severe degradation occurs, resulting in reduced mechanical properties.

[0074] In one embodiment, the polylactic acid prepared in step (1) in step (3) is mixed with the PBSA / HA mixture obtained in step (2), and then added to a twin-screw extruder and extruded at a temperature of 180 to 200° C., for example, 180° C., 185° C., 190° C., 195° C., 200° C. or any range or point value therebetween; and extruded at a screw speed of 100 to 200 rpm, for example, 100 rpm, 120 rpm, 140 rpm, 160 rpm, 180 rpm, 200 rpm or any range or point value therebetween.

[0075] In this article, the high-performance implantable biomedical product is prepared by the microinjection molding process described in step (4), and different implantable medical products, such as bone nails, can be prepared by different microinjection molds.

[0076] In one embodiment, the process conditions of the micro injection molding process in step (4) are: an injection speed of 50 to 600 mm / s, for example, 50 mm / s, 70 mm / s, 80 mm / s, 90 mm / s, 100 mm / s, 120 mm / s, 140 mm / s, 160 mm / s, 180 mm / s, 200 mm / s, 220 mm / s, 250 mm / s, 300 mm / s, 350 mm / s, 400 mm / s, 450 mm / s, 500 mm / s, 550 mm / s, 600 mm / s or any range or point value therebetween; a mold temperature of 20 to 60° C., for example For example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or any range or point value therebetween; melt temperature 180-200°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C or any range or point value therebetween; holding and cooling time 5-15s, for example, 5s, 6s, 7s, 8s, 9s, 10s, 11s, 12s, 13s, 14s, 15s or any range or point value therebetween, the holding and cooling time may be the same or different; and the shear rate of the blend at the gate in the micro injection molding machine is controlled to be 50000-70000s -1 , for example 50000s -1 , 52000s -1 , 54000s -1 , 56000s -1 , 58000s -1 , 60000s -1 , 62000s -1 , 64000s -1 , 66000s -1 , 68000s -1 , 70000s -1 or any range or point value in between.

[0077] In this article, the addition amount of polybutylene succinate adipate (PBSA) is limited to 10-20 parts because the inventors of the present invention have found in the actual production process that the addition of PBSA in the micro injection molding process can obviously improve the elongation at break of PLA, but its essence is to form a fibrous structure under certain process conditions. However, when the PBSA content increases, the strength and modulus of the product decrease significantly. In order to improve the elongation at break while maintaining high strength and modulus, the addition amount of PBSA is limited to 10-20 parts, and more preferably 10-15 parts. With reference to the technical solution of the present invention, the material obtained by preparing the obtained material at a PBSA addition amount of 10% shows a material mechanical property significantly higher than the material mechanical property of the same proportion PBSA addition amount prepared by traditional injection molding, and even much higher than the material mechanical property of the material mechanical property of the preferred proportion PBSA addition amount in the traditional injection molding preparation technology. According to the inventors of the present invention, micro injection molding can produce a certain temperature and shear stress gradient in the thickness direction of the mold cavity, thereby forming a "skin layer-core layer" structure in the micro injection molding sample. The morphology images at different positions along the thickness direction show that the PBSA dispersed phase basically exists in the skin layer in the form of spherulites or ellipsoids, while in the shear layer and core layer, the PBSA dispersed phase can form long and interlocking fibrous structures.

[0078] Further, the process conditions of the micro injection molding process described in step (4) include an injection speed of 50 to 600 mm / s. The inventors of the present invention found during the experiment that different injection speeds include 0 mm / s (replaced by hot pressing), 20 mm / s, 50 mm / s and 100 mm / s. In the morphology comparison results, it can be seen that the injection speed has a great influence on the morphology formation. For the hot pressing molded sample (here refers to the injection speed = 0 mm / s), an island structure is formed, and the PBSA dispersed phase does not undergo fiberization. In contrast, under micro injection molding conditions, when the injection speed is in the range of 20 to 100 mm / s, the PBSA dispersed phase structure formed is completely different. In the PLA continuous phase matrix, HA filler particles are contained, forming a large number of fibrous structures of the PBSA dispersed phase. With the increase of the injection speed (20→100 mm / s), the aspect ratio, orientation degree and number of the fibrous structure of the PBSA dispersed phase also show a significant increasing trend. The formation mechanism involved is attributed to the presence of an extremely strong shear stress field under microinjection molding conditions, which induces the PBSA dispersed phase to form a clear fibrous structure. During the microinjection molding process, the deformation, stretching and orientation of the PBSA dispersed phase droplets along the melt flow direction lead to the formation of fibrous structures. Higher injection speeds lead to the generation of a stronger shear stress field, which in turn leads to the formation of a larger number of fibrous structures of the PBSA dispersed phase with a higher aspect ratio.

[0079] However, due to the differences in micro-injection molded products, and considering that the polymer fluid velocity field distribution depends on the mold structure size, the rheology of the polymer material, the thermal conductivity, the specific processing technology, and the melt flow rate that the injection molding machine can provide, not all micro-injection molding process conditions can make the shear rate equivalent to the range corresponding to the 50-600 mm / s injection speed of the injection molding machine used by the inventor. Therefore, it is particularly important to study at what shear rate a microfibrillated structure can be formed, so as to provide theoretical guidance for product design and process optimization. In view of this, the present invention performs a computer simulation of the injection molding process of PLA / PBSA, calculates the shear rate generated when the melt flows through the gate, and finds that the melt shear rate exceeds 150,000s -1 When the shear rate is 60000s -1 When the shear rate at the gate is 50000~70000s -1 When the fiber morphology of the prepared product is good, the mechanical properties are significantly improved; in this way, those skilled in the art can use fluid finite element simulation software Polyflow to design the gate and runner in advance when designing the product according to the above data, or optimize the processing technology during the actual production process, so that the shear rate at the flow field is at or near the optimal level, thereby reducing the workload of process control.

[0080] In one embodiment, the mold temperature in step (4) is preferably 25-35°C. PBSA, as a dispersed phase, is stretched by the shear flow field to become a fiber, and its specific surface area increases significantly, which is an entropy reduction process. The effect of surface tension causes it to undergo sinusoidal disturbances, which in turn leads to fiber breakage, so a fast cooling rate is required to fix its morphology. According to traditional mold heat transfer theory, the cooling rate of injection molded products during the cooling process is mainly determined by the melt temperature, mold temperature and thermal conductivity of the material. The inventors of the present invention have found in their research that mold temperature has a very large influence on the fibrosis of PBSA, especially for the preparation of micro medical devices with a local thickness of about 0.33 mm and a relatively large area in the perpendicular thickness direction, such as vascular clamps. When the mold temperature is 50°C, the formed fibrous structure is easily broken into small droplets, but when the mold temperature drops to 40°C, it is more fibrous with a few droplets. When the mold temperature drops to 30°C, the droplets almost disappear, and string crystals are attached to the fiber surface. This is mainly because the overall cooling rate inside the product is extremely fast due to the lower mold temperature, and the fibers are cooled and fixed before they can deform or break. When the mold temperature is 25-35°C, the microfiber structure of the product is easier to preserve. The optimization of this technical content has guiding significance for actual production and processing. In some medical products such as micro vascular clips, the curved part is thinner and cools faster, and it is the key part. Whether the internal morphology of this part, that is, the fibrotic structure, can be cooled and fixed in time often determines whether the product is usable.

[0081] In addition, it is well known in the art that in traditional polymer injection molding, the thickness of the injection molded product is relatively uniform, the shear rate is low, and it is difficult to use its own structure to produce in-situ fiberization. Therefore, if it is necessary to improve the mechanical properties of such products through fibrotic structures, the shear rate at the runner and gate during the micro injection molding process will be crucial for the formation of fibrotic structures. For example, for medical devices such as vascular clips and bone nails, those skilled in the art can design the dimensions of the runner or gate based on the technical content of the present invention to construct a shear-stretching flow field to guide actual production and processing.

[0082] It is worth noting that the micro-injection molding machines used in the micro-injection molding process often have large differences in injection pressure and injection speed in their processing conditions due to different models, product requirements and actual conditions. The present invention eliminates the differences caused by different processing environments by providing the shear rate at the runner and the gate during the injection molding process. This enables technical personnel in this field to determine the specific processing conditions suitable for the current processing environment by simulating and calculating the shear rate, and stably obtain high-performance implantable biomedical products with a fibrotic structure without having to perform pre-production operations such as trial molds, thereby greatly reducing production costs.

[0083] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0084] Example

[0085] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.

[0086] 1. Raw materials

[0087] PLA uses commercially available poly(L-lactic acid) (PLLA) 4032D, containing 2% poly(D-lactic acid) (PDLA), produced by NatureWorks, USA;

[0088] Polybutylene succinate adipate (PBSA) 5001MD, purchased from Showa Denko;

[0089] Hydroxyapatite (HA) was purchased from Aladdin Reagents.

[0090] 2. Preparation method

[0091] (1) Prepare the following raw materials by weight:

[0092] Polylactic acid (PLA) 88-89 parts,

[0093] 10 parts of polybutylene succinate adipate (PBSA),

[0094] Hydroxyapatite (HA) 1-2 parts,

[0095] Wherein, the polylactic acid, polybutylene succinate adipate and hydroxyapatite are 100 parts in total;

[0096] (2) melt-blending the polybutylene succinate adipate prepared in step (1) with hydroxyapatite in an internal mixer to prepare a PBSA / HA mixture;

[0097] The process parameters for melt blending in the internal mixer are: rotor speed of 60 rpm, blending time of 5 minutes, and temperature of 120°C;

[0098] (3) mixing the polylactic acid prepared in step (1) with the PBSA / HA mixture obtained in step (2), adding the mixture to a twin-screw extruder and extruding the mixture at 180° C. and 100 rpm, and using a traction machine to stably traction the extruded filaments, cooling and pelletizing the mixture to obtain PLA / PBSA / HA pellets;

[0099] (4) injecting the PLA / PBSA / HA pellets obtained in step (3) into the bone screw mold cavity in a micro injection molding machine (MicroPower 15, Wittmann Battenfeld GmbH, Austria) to prepare a high-performance implantable biomedical product through a micro injection molding process;

[0100] Among them, the process conditions of the micro injection molding process are: injection speed 100mm / s, mold temperature 30℃, melt temperature 180℃, holding time 5s, cooling time 15s, and injection pressure of 1600MPa.

[0101] 3. Test methods

[0102] The microstructure was observed on a field emission scanning electron microscope (SEM) InspectF (FEI, Finland) with an accelerating voltage of 5 kV. The melting behavior of micro injection molded samples was studied on a differential scanning calorimeter Q200 (TA, USA). The tensile strength was tested at 25°C using an Instron tester (Instron 5569) with a displacement speed of 2 mm / min. The bending test of bone nail samples was performed on an Electro-Force 3220 SERIES II tester (Bose, USA). The mechanical properties of all samples were measured at least five times.

[0103] The water contact angle test was performed using a German KrussDSA100 contact angle tester. The rheological behavior was studied using a flat plate rheometer (AR2000ex, TA Company). The internal structure of the sample was analyzed using a two-dimensional small-angle X-ray scattering (SAXS) instrument (Xeuss2.0, France). The crystalline structure of the sample was studied using X-ray diffraction (XRD), with a voltage of 40 kV and a scanning speed of 5° / min.

[0104] 3.1 Cell acquisition and culture

[0105] Mouse preosteoblast cell line MC3T3-E1 was collected and cultured in α-modified Eagle medium (GIBCO, New York, USA) supplemented with 10% fetal bovine serum and 1% penicillin / streptomycin at 37°C and 5% carbon dioxide. After five days, the cells reached 85%-90% confluence in the culture dish. The adherent cells were cultured in complete medium, digested with trypsin / EDTA after fusion, and collected for further experiments.

[0106] 3.2 In vitro cytocompatibility assessment

[0107] The prepared micro-bone nails were subjected to in vitro degradation experiments: PPH0, PPH1, PPH2 and PPH4 micro-bone nails of equal mass were first soaked in sterile phosphate buffered saline (PBS) and then placed in an incubator at 37°C and 5% carbon dioxide. After 1-4 weeks of treatment, the residual weight of the treated samples was weighed. The proliferation of MC3T3-E1 cells on the micro-bone nails was detected using CCK-8 and MTT kits. After 1-7 days of culture, the nails were removed from the culture medium and rinsed three times with PBS. MC3T3-E1 cells with the same seeding density were co-cultured with the micro-bone nails for 1, 4 and 7 days and stained with Calcein-acetoxymethyl ester (AM) / Propidium Iodide (PI) reagent. The cell death and live cell staining results were observed using a polarized optical microscope (POM) (Leica, Germany). Fluorescein Diacetate (FDA) will stain live cells green, and Propidium Iodide (PI) will stain dead cells red. The morphology of cells after 1, 4 and 7 days was observed using SEM. Before SEM analysis, the samples were rinsed with PBS and then fixed in glutaraldehyde for 2 hours. A series of ethanol solutions (30%, 50%, 70%, 90% and 100%) were used for dehydration in sequence, each for 15 minutes, and then the ethanol was dried at room temperature. The upper surface with cells was treated with gold sputtering and observed using SEM.

[0108] 3.3 In vivo biological evaluation (surgical model)

[0109] Experiments on femoral defect models were performed using New Zealand rabbits provided by the Experimental Animal Center of Sichuan University, and all experiments were approved by the Ethics Committee of Sichuan University. The surgery was performed under sterile conditions and anesthesia was performed by injection of sodium pentobarbital and Simexin II. The skin and muscles were cut layer by layer to expose the femur, and then a circular defect with a diameter of 3 mm was drilled on the femur. Micro-bone screws were then implanted. In the experiment, PPH0, PPH1, PPH2 and PPH4 screws were implanted in the femur of rabbits for comparison, and penicillin was injected three days after surgery to prevent infection. The rabbit femurs were removed 1 month and 3 months after surgery and washed with PBS. The attached tissues were washed with a mixture of PBS (90wt%) and pepsin (10wt%) and then fixed with 4% paraformaldehyde. The fixed samples were dehydrated using gradient ethanol solutions (60%, 80%, 95% and 100% concentrations) and then embedded in resin. The embedded tissues were cut into 5 μm thick sections and stained with hematoxylin-eosin (HE) and Masson's staining for histological analysis.

[0110] 3.4 Statistical analysis

[0111] One-way analysis of variance (ANOVA) and Bonferroni post hoc comparisons were used to evaluate differences between different groups. All in vitro experiments were repeated three times and at least twice. P values ​​< 0.05 were considered significant. All statistical analyses were performed using GraphPad Prism 8.0 software.

[0112] Example 1

[0113] Example 1 was prepared with reference to the above “2. Preparation method”, wherein hydroxyapatite was 1 part, that is, the HA content in the raw material was 1 wt%, and the high-performance implantable biomedical product obtained was a bone nail sample, recorded as PPH1.

[0114] Example 2

[0115] Example 2 was prepared with reference to the above “2. Preparation method”, wherein hydroxyapatite was 2 parts, that is, the HA content in the raw material was 2 wt %, and the obtained high-performance implantable biomedical product was a bone nail sample, denoted as PPH2.

[0116] Comparative Example 1

[0117] Comparative Example 1 was prepared with reference to the above “2. Preparation method”, but without adding hydroxyapatite, that is, the HA content in the raw material was 0 wt %, and the obtained bone screw comparison sample was prepared and recorded as PPH0.

[0118] Comparative Example 2

[0119] Comparative Example 2 was prepared with reference to the above “2. Preparation method”, wherein 4 parts of hydroxyapatite, namely, the HA content in the raw material was 4 wt%, and the obtained bone screw comparison sample was prepared and recorded as PPH4.

[0120] Comparative Example 3

[0121] Comparative Example 3 is to prepare PLA / PBSA / HA pellets by referring to steps (1) to (3) of "2. Preparation method" above, wherein hydroxyapatite is 2 parts, that is, the HA content in the raw material is 2wt%; then the PLA / PBSA / HA pellets are hot-pressed to form a PLLA / PBSA / HA composite sample, and the sample preparation conditions involved are as follows: the PLA / PBSA / HA pellets are added to the mold frame, preheated at 180°C for 2 minutes, then hot-pressed for 5 minutes, and finally cold-pressed at 40°C for 3 minutes.

[0122] Comparative Example 4

[0123] Comparative Example 4 was prepared with reference to the above “2. Preparation method”, wherein hydroxyapatite was 2 parts, i.e., the HA content in the raw material was 2 wt%, but the injection speed in step (4) was 20 mm / s, and the resulting bone screw comparison sample was prepared.

[0124] Example 3

[0125] Example 3 was prepared with reference to the above “2. Preparation method”, wherein hydroxyapatite was 2 parts, i.e., the HA content in the raw material was 2 wt%, but the injection speed in step (4) was 50 mm / s, and the high-performance implantable biomedical product obtained was a bone screw sample.

[0126] Comparative Example 5

[0127] The PLA raw material was injected into the bone screw mold cavity in a micro injection molding machine (MicroPower 15, Wittmann Battenfeld GmbH, Austria), and the obtained bone screw comparison sample was prepared by micro injection molding process;

[0128] The conditions of the micro injection molding process are as follows: injection speed 100 mm / s, mold temperature 30°C, melt temperature 180°C, holding time 5s, cooling time 15s, and injection pressure 1600MPa.

[0129] 4. Test results

[0130] The formation of the "island" structure is the key factor affecting the in-situ formation of PBSA fibers. The morphology and structure of the intermediate composite material were analyzed by SEM. Figure 1 (a) to (d). Obviously, both PLA / PBSA and PLA / PBSA / HA composites exhibit an “island” structure, in which PLA is the continuous phase and spherical PBSA particles are the dispersed phase. In addition, in addition to the distribution of HA within the PBSA dispersed phase particles, HA particles are also distributed in the PLA matrix, indicating that they migrated into the PLA matrix during the extrusion process. The migration behavior of HA particles has been further confirmed by TEM images ( Figure 2 ). It is worth noting that Figure 1 As shown in (b) to (d), HA particles are evenly dispersed without obvious agglomeration. Statistical analysis was performed on the SEM images. The results ( Figure 3 ) showed that HA content did not affect the average particle size or particle size distribution of the dispersed phase. In addition, gaps were observed at the interface between the matrix and the dispersed phase, which may be caused by the difference in volume reduction caused by their different crystallization abilities or interfacial compatibility issues.

[0131] Like traditional injection molding, the micro injection molding process can also generate temperature and shear stress gradients in the thickness direction of the mold cavity, thereby forming a "skin-core" structure in the micro injection molded part samples. The morphology images at different positions along the thickness direction show that the PBSA dispersed phase basically exists in the skin layer in the form of spherulites or ellipsoids, while in the shear layer and core layer, the PBSA dispersed phase forms a long and interlocking fibrous structure. The morphology of PBSA fibers in the matrix is ​​the key to the mechanical properties of the PLA matrix. Therefore, our attention is focused on characterizing the morphology and distribution of PBSA fibers in the core layer. We used SEM to observe the brittle fracture surface of the micro injection molded samples along the flow direction, and the results are shown in the following figure. Figure 1 As shown in (a-1) to (d-1). In the PLA / PBSA two-phase system, a high aspect ratio PBSA dispersed phase structure exists in the PLA matrix. For samples containing 1wt% and 2wt% HA, PBSA fibers can be observed on the quenched section, while HA particles appear in agglomerated form in the PLA matrix. However, when the HA content is 4wt%, there are difficult to identify PBSA fibers on the quenched section, and only agglomerated HA particles can be observed on the rough quenched section. To further verify our findings, we etched the sample quenched section to remove the amorphous PLA, and the results are shown in Figure 2. Figure 1 As shown in (a-2) to (d-2), it can be seen that PBSA dispersed phase fibers oriented along the melt flow direction were observed in PPH0, PPH1 and PPH2 samples. However, for PPH4 sample, it became difficult to observe PBSA fibers with a high aspect ratio.

[0132] In order to further study the fiberization mechanism of PBSA dispersed phase, the effect of injection speed on the morphology evolution of PLA / PBSA / HA composite system during micro injection molding was also carefully studied. The different injection rates used included 0 mm / s (replaced by hot pressing), 20 mm / s, 50 mm / s and 100 mm / s. The morphology results are shown in Figure 2. Figure 4As shown in the figure, it can be seen that the injection rate has a great influence on the morphology formation. For the hot press molded sample (here, the injection speed = 0 mm / s), an island structure is formed, and the PBSA dispersed phase does not undergo fiberization. In contrast, under micro injection molding conditions, when the injection speed is in the range of 20-100 mm / s, the structure of the PBSA dispersed phase formed is completely different. In the PLA continuous phase matrix, HA filler particles are contained, forming a large number of fibrous structures of the PBSA dispersed phase. With the increase of injection speed (20→100 mm / s), the aspect ratio, orientation degree and number of the fibrous structure of the PBSA dispersed phase also show a significant increasing trend. The formation mechanism involved is attributed to the existence of an extremely strong shear stress field under micro injection molding conditions, which induces the PBSA dispersed phase to form a clear fibrous structure. During the micro injection molding process, the shear deformation, stretching and orientation of the PBSA dispersed phase droplets along the melt flow direction lead to the formation of fibrous structures. Higher injection rates lead to the generation of stronger shear stress fields, resulting in the formation of more fibrous structures of the PBSA dispersed phase with higher aspect ratios.

[0133] The successful formation of the oriented PBSA fiber structure during the micro-injection molding process was confirmed by SEM analysis, and then tensile tests were carried out to determine the relevant mechanical properties and investigate the effect of HA content on the material properties. Figure 5 (a) and Figure 5 (b) shows the stress-strain curves and specific mechanical property parameters of the samples, respectively. It is obvious that pure PLA exhibits typical brittle fracture behavior after reaching the maximum tensile strength. In contrast, due to the in-situ formation of PBSA fibers, the samples containing PBSA show improved fracture resistance and exhibit a tensile yield process within the curve, effectively improving the toughness of the material. Analysis Figure 5 The specific data in (b) show that the elongation at break of pure PLLA is 5.4%; after adding 10wt% PBSA, the elongation at break increases to 53.2%; after further adding 1wt%, 2wt% and 4wt% HA, the elongation at break reaches 59.4%, 51.3% and 41%, respectively, indicating that the toughness is enhanced compared with pure PLLA. Interestingly, after adding 1wt% HA, a significant increase in elongation at break is observed. However, with the increase of HA content, a downward trend in elongation at break is observed, which is consistent with the general performance change trend of HA as a filler in composite materials.

[0134] Based on the inherent brittleness of PLA, it is necessary to have a deeper understanding of the fracture mechanism of toughened PLA. First, the tensile fracture surfaces of the PPH2 sample perpendicular to and parallel to the tensile direction were observed using SEM. Figure 5(c) and (d) show that on the cross section parallel to the melt flow direction, a large number of PBSA fibers dispersed in the PLA matrix can be observed, as well as voids caused by fiber-matrix interface destruction and fiber breakage due to stretching.

[0135] SEM images provide an intuitive representation of the plastic deformation of the matrix during tensile testing. However, it is difficult to characterize the changes in the internal crystalline structure of the sample using SEM alone. Therefore, we used two-dimensional small-angle X-ray scattering (2D-SAXS) to study the internal molecular orientation of PPH0 and PPH2 samples after tensile testing. The results are shown in Figure 2. Figure 5 As shown in (e) and (f), diamond-shaped scattering fringes appear in the 2D-SAXS spectra, indicating that the internal molecular chains of the material are significantly oriented after stretching. In contrast, the unstretched sample only shows annular fringes. The appearance of diamond-shaped scattering fringes in PPH2 indicates that not only the polymer molecular chains are oriented, but also the HA particles are arranged along the stretching direction.

[0136] The ternary composite micro bone screw was successfully produced by micro injection molding. Figure 6 As shown in (a), the bone screw has a good appearance without any obvious defects such as short shot, warping or flashing. Figure 6 The SEM images in (d) and (e) further confirm that the structure of the bone screw is clear and the thread is smooth and complete (only tens of microns wide). Figure 6 (f) shows the quenched cross-section of the bone screw along the melt flow direction. After etching, PBSA fibers are evenly distributed in the PLA matrix and oriented along the flow direction, indicating that the fiber structure is successfully formed in situ in the bone screw. Figure 6 (b) shows the photos of the bone nails before and after the three-point bending test, indicating that all samples remained intact during the bending test, which is attributed to the presence of PBSA fibers. Studying the internal structure of the bone nail is crucial to understanding the mechanism of material toughness enhancement. Therefore, SEM was used to observe the quenching cross-section morphology of the bone nail along the direction perpendicular to the melt flow. Figure 6 As shown in (g), obvious plastic deformation and tearing behavior were observed on the cross section of the bone screw. After further magnification, the cross section appeared very rough, with obvious fiber fracture, indicating that the toughness of the PLA-based bone screw is very strong. Figure 6 (i) shows the load-displacement curves of the bending test, indicating that the maximum bending load of the bone screw increases with the increase of HA content. The slope of the load-displacement curve represents the bending modulus of the sample, reflecting its resistance to bending deformation. It is worth noting that the slope of the load-displacement curves of all bone screws remains consistent, indicating that HA has little effect on the bending modulus of the bone screw. In addition, the load-displacement curves show a bending recovery process, which once again confirms the good toughness of PLA-based bone screws.

[0137] The cytotoxicity of the bone nails in different groups was further explored in detail using the calcein-AM / PI staining method. Figure 7 As shown. Under the same culture conditions, cells co-cultured with various bone screw groups showed obvious proliferation without obvious cytotoxicity. The in vitro experimental results of bone screws showed that with the increase of HA ratio, the degradation rate of bone screws decreased, which was beneficial to the growth of MC3T3-E1 cells. However, in clinical applications, the degradation rate of degradable bone screws must be consistent with the healing rate of bone structure, not faster.

[0138] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a high-performance implantable biomedical product based on polylactic acid, characterized in that The main steps include: (1) Prepare the following raw materials by weight: Polylactic acid 78-89 parts, 10 to 20 parts of polybutylene succinate adipate, 1-2 parts of hydroxyapatite, Wherein, the polylactic acid, polybutylene succinate adipate and hydroxyapatite are 100 parts in total; (2) preparing a PBSA / HA mixture by melt blending the polybutylene succinate adipate prepared in step (1) and hydroxyapatite; (3) mixing the polylactic acid prepared in step (1) with the PBSA / HA mixture obtained in step (2), adding the mixture to a twin-screw extruder and extruding the mixture at 180-200° C. and 100-200 rpm, and using a traction machine to stably traction the extruded filaments, cooling and pelletizing the mixture to obtain PLA / PBSA / HA pellets; (4) injecting the PLA / PBSA / HA pellets obtained in step (3) into a desired product mold cavity in a micro injection molding machine, and preparing a high-performance implantable biomedical product through a micro injection molding process; The process conditions of micro injection molding are as follows: injection speed 50-600 mm / s, mold temperature 20-60°C, melt temperature 180-200°C, holding pressure and cooling time 5-15s, and the shear rate of the blend at the gate in the micro injection molding machine is controlled to be 50,000-70,000s. -1 .

2. The preparation method according to claim 1, characterized in that: The polylactic acid in step (1) includes any one of polylactic acid types 4032D, 6201D, 3251D and 7000D.

3. The preparation method according to claim 1, characterized in that: The step (2) comprises melt blending the polybutylene succinate adipate prepared in the step (1) with hydroxyapatite to prepare a PBSA / HA mixture, specifically melt blending the prepared polybutylene succinate adipate with hydroxyapatite in an internal mixer to prepare a PBSA / HA mixture; The process parameters for melt blending in the internal mixer are as follows: rotor speed is 30-80 rpm, blending time is 5-7 minutes, and temperature is 110-130°C.

4. The preparation method according to claim 1, characterized in that: The PLA / PBSA / HA pellets are obtained by cooling and pelletizing in step (3), and the particle size of the PLA / PBSA / HA pellets is 0.5 to 2 mm.

5. The preparation method according to claim 1, characterized in that: The amount of polybutylene succinate adipate in step (1) is 10 to 15 parts.

6. The preparation method according to claim 1, characterized in that: The mold temperature in step (4) is 25-35°C.

7. A high-performance implantable biomedical product prepared by the method for preparing a high-performance implantable biomedical product based on polylactic acid as claimed in claim 1.

8. The high-performance implantable biomedical product according to claim 7, characterized in that: The high-performance implantable biomedical product is a bone nail.

Citation Information

Patent Citations

  • Methods for fabricating PLA biomedical microdevices using micro-injection molding

    CN110815700B

  • A method for preparing high-performance PLA / PBSA micro-articles based on micro-injection molding process

    CN114228086B

  • Method for preparing high-performance PLA / PBSA miniature product based on miniature injection molding process

    CN114228086A

  • Method and apparatus for treating bone fractures, and / or for fortifying and / or augmenting bone, including the provision and use of composite implants, and novel composite structures which may be used for medical and non-medical applications

    EP3154444A1

  • Biodegradable polymer blend

    GB201218637D0